Digital Social Research: Topics and Methods - Delli Paoli, Angela; Masullo, Giuseppe (Italian Sociological Review, 2022)
The digital transformation of social life should be accompanied by new forms of social enquiry. In particular, the digital would make possible new forms of understanding sociality that arise from the complex interactions between digital technology, social research and social life. It invades the micro, meso and macro areas and aspects of social life (citizenship, identity, gender and sexuality, power relations, inequalities, social networks social structures and institutions, politics and economics, to name but a few) and generates new practices, socialisation processes, ties and relationships, re-distributing power among institutional actors. Apart from skepticism or enthusiasm, the paper investigates the distinctive topics of digital social research, the nature of digital data, and the place for technological objects (devices, technology, robots, AI, algorithms, etc.), the digital biases (e.g. digital social desirability, digital discriminations, etc;), the methodological challenges and opportunities deriving from acquiring records of computer-mediated social interactions being them self-report on individual’s social network or digital traces left by individual’s online activities and the methodological principles which are not easily dismissed by the new availability of data.